Tumor-associated tissue eosinophilia in preinvasive and invasive squamous cell carcinoma of cervix - Radhika C Sasturkar; Ramesh BH; Sunita Nyamagoudar; Sateesh S Jigjini (Journal of Pathology of Nepal)
Background: Differentiating between preinvasive and invasive squamous neoplasms of the cervix can be a challenge in small, superficial fragments of cervical biopsy, particularly when inflammatory infiltrates obscure the epithelial stroma interface and due to tangential sectioning of the acanthotic squamous epithelium. This study evaluates whether thresholds of eosinophils in stroma serve as a morphological marker for the presence of tumor invasion in squamous neoplasms of the cervix.